The Wisconsin Upper Respiratory Symptom Survey is responsive, reliable, and valid - Barrett, Bruce (J Clin Epidemiol, 2005)
OBJECTIVE: To assess reliability, responsiveness, importance to patients, and convergent validity for the Wisconsin Upper Respiratory Symptom Survey (WURSS-44) and to develop a short-form WURSS. STUDY DESIGN AND SETTING: Community-based recruitment of participants with colds. Prospective monitoring from within 48 hours of first symptom until 2 days after end of cold. The WURSS-44 includes 1 global illness severity item, 32 symptom-based items, 10 functional quality-of-life items, and 1 item assessing global change. The SF-36, SF-8, and the Jackson cold scale were used as external comparators. RESULTS: Participants included 104 women and 45 men, aged 18 to 80 years, self-reporting on 1,681 person-days of illness. Factor analysis suggested 10 dimensions, with reliability coefficients from 0.62 to 0.93. Comparing daily WURSS-44 to Jackson and SF-8 yielded Pearson correlation coefficients from 0.73 to 0.93, and from −0.60 to −0.84, respectively. Importance to patients and responsiveness assessment yielded a short version, the WURSS-21. Guyatt's responsiveness index was 0.54 for the SF-8, 0.61 for the Jackson, 0.71 for the WURSS-44, and 0.80 for the WURSS-21, suggesting that a two-armed trial would require 74 participants for the WURSS-21, 92 for the WURSS-44, 124 for the Jackson scale, and 156 for the SF-8. CONCLUSIONS: The construct validity of WURSS-44 is supported by measures of reliability, responsiveness, importance to patients, and convergence. A shorter version, the WURSS-21, may be even more responsive.